The influence of electronic word of mouth on customer satisfaction with innovation and service quality as mediating variables - Amanda Febry Arani Siti Azizah; Ratna Roostika (Institute of Computer Science (IOCS), 2023)
The type of research used is explanatory research. The research was conducted to test the relationship between variables, namely electronic word of mouth (X), service innovation (Z1), service quality (Z2), and participant satisfaction (Y). The population in this study were BPJS Employment Yogyakarta participants who used the Service Without Physical Contact (Lapak asik). Lapak Asik is a media for submitting Old Age Insurance (JHT) claims. The minimum sample size in this research is 200 respondents. The sampling technique uses non-probability techniques. The data collection technique in this research is by distributing questionnaires. The data analysis technique used in this research is Smart PLS software. The data used in this research is quantitative data. The data collection technique in this research is by distributing questionnaires. Based on the research results, empirical facts were obtained in the form of: 1) Electronic word of mouth influences service innovation positively and significantly; 2) Electronic word of mouth influences service quality positively and significantly; 3) Service innovation cannot affect the satisfaction of Yogyakarta BPJS Employment participants; 4) Service quality influences the satisfaction of Yogyakarta BPJS Employment participants positively and significantly; 5) Electronic word of mouth influences BPJS Employment Yogyakarta Participant Satisfaction positively and significantly